2013
DOI: 10.5539/jas.v5n8p216
|View full text |Cite
|
Sign up to set email alerts
|

Crop Load and Time of Thinning Interact to Affect Fruit Quality in Sweet Cherry

Abstract: Balanced crop load is key to the production of export-quality cherries. We investigated the level and timing of crop load regulation on fruit quality. Additionally we sought to investigate possible correlation between firmness estimated by compression test or flesh penetrability. Fruit diameter was similar between 1 and 2 bud/spur treatments but was significantly lower in the 4 bud/spur treatment at all thinning times in 'Van' in the 2010/11 season. In contrast 'Sweetheart' fruit diameter was only decreased at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 24 publications
(10 reference statements)
3
25
0
2
Order By: Relevance
“…Harvest maturity was uniform in both varieties with the difference in fruit size an observed and supported varietal characteristic (De Franceschi et al, 2013;Measham et al, 2009). The crop should not have experienced any loss of size as a result of cropload or yield because the threshold for size reduction was not reached (Bound et al, 2013;Measham et al, 2009Measham et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Harvest maturity was uniform in both varieties with the difference in fruit size an observed and supported varietal characteristic (De Franceschi et al, 2013;Measham et al, 2009). The crop should not have experienced any loss of size as a result of cropload or yield because the threshold for size reduction was not reached (Bound et al, 2013;Measham et al, 2009Measham et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in fruit size would not have been a result of different croploads because there was only a weak relationship between bud or flower numbers as a result of pruning treatments. Moreover, it was unlikely that loads were sufficient to induce a decrease in fruit size (Bound et al, 2013). Furthermore, Measham et al (2013) showed that pruning at Stage II of fruit development negatively impacted the current season's fruit quality indicating a competitive interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Cropload (or simply the number of fruit per tree) can also influence fruit sugars in the current season (Bound et al, 2013;Measham et al, 2012;Roper et al, 1988). Klages et al (2001) found a decrease in starch and an increase in glucose in apple fruit from trees with low croploads, whereas Roussos et al (2011) found a decrease in glucose in apricot (Prunus armeniaca) fruit from low-cropping trees but no impact on total soluble solids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of crop load regulation either by winter or summer pruning (e.g., heading-back and tipping cuts), thinning (i.e., removal of buds, flowers, or fruits), or both cause an imbalance between reproductive and vegetative growth in dwarf and semidwarf sweet cherry combinations using 'Gisela' rootstocks (Gutzwiler and Lang, 2001;Wang et al, 2003;Whiting et al, 2005), resulting in premature tree aging and low-quality fruit. Lack of crop load regulation reduces size, SSC, and firmness in the fruits of sweet cherry (Ayala and Lang, 2008;Bound et al, 2013;Villasante et al, 2012;Whiting et al, 2005;Whiting and Lang, 2004).…”
mentioning
confidence: 99%